The Relationship Between Knowledge of Dental and Oral Health and The Number of Functioning Teeth in Indonesian Elderly People - Deby Anggraeni; Isnanto; Ida Chairanna Mahirawatie; Tanvish Nitin Manwatkar (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
Tooth loss is a cause of decreased masticatory function that affects the oral cavity and general health in the elderly. The elderly was expected to have at least 20 working teeth, meaning that the masticatory, aesthetic and speech functions were considered normal, although less than 32 teeth. This study aims to determine the relationship between the dental and oral health of the elderly with the number of functioning teeth at the Hargo Dedali Nursing Home in Surabaya. This type of research is analytic with a cross sectional design. The total population is 38 elderly and the research sample is 35 elderly using random sampling technique with purposive sampling. Method analyzed technique uses the Pearson Correlation test. The result of this research is the elderly population is female. Their age range is between 60-92 years. Questions were answered correctly overall by 48.1%. The most questions answered incorrectly about tooth loss by 67.9%. There are 3 elderly who have 20 working teeth. The average working gear is 9.3 or 9 teeth per person. Data are normally distributed. There is a relationship between the two variables (0.000 < 0.05). Conclusion of this research is smaller the value of dental and oral health knowledge of the elderly, the less the number of teeth that work. The benefits of this research can provide awareness and motivation for families, nursing home managers, health workers in an effort to serve dental and oral health in the elderly.